Tualang honey promotes apoptosis of the A549 lung adenocarcinoma cell line via modulation of PI3K/AKT signaling pathway-related proteins - Nazirah A; Puteri Shafinaz Abdul-Rahman (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
The phosphatidylinositol 3-kinases (PI3Ks)/protein kinase B (AKT) signaling pathway is frequently overexpressed in lung adenocarcinoma and associated with carcinogenesis through cell proliferation, and apoptosis deactivation; and it also enhances chemotherapeutic drugs resistance. Tualang honey (TH) has proven anticancer property on lung adenocarcinoma. However, the underlying mechanisms remain unreported. Hence, this study investigates the apoptosisinducing effect of TH on A549 lung adenocarcinoma cell line using RayBio® Human Apoptosis Array and label-free quantitative liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis to elucidate the modulation of upstream and downstream proteins of PI3K/AKT signaling pathway. The apoptosis-promoting effects of TH were associated with (i) the upregulation of pro-apoptotic proteins (i.e. cytochrome c, histone H1.2, and histone H1.4) and tumor suppressor proteins (i.e. IGFBP-3 and IGFBP-5), and (ii) downregulation of XIAP, insulin-growth factor (IGF) system (i.e. IGF-1, IGF1R, IGFBP-1, IGFBP-2, and IGFBP-4), HSP90AB1, YWHAQ, endoplasmin, and ITGB1. The effects were also linked with the suppression of receptor tyrosine kinase, integrins, G proteins, CHUK, RAC1, and JAK. Thus, TH may promote apoptosis of A549 lung adenocarcinoma cell line through alteration of the PI3K/AKT signaling pathway-related proteins. However, further studies involving animal models to provide a better model of understanding would prove necessary.